2008
DOI: 10.1073/pnas.0803242105
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic evidence for multiple losses of flight in ratite birds

Abstract: Ratites (ostriches, emus, rheas, cassowaries, and kiwis) are large, flightless birds that have long fascinated biologists. Their current distribution on isolated southern land masses is believed to reflect the breakup of the paleocontinent of Gondwana. The prevailing view is that ratites are monophyletic, with the flighted tinamous as their sister group, suggesting a single loss of flight in the common ancestry of ratites. However, phylogenetic analyses of 20 unlinked nuclear genes reveal a genome-wide signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
228
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(251 citation statements)
references
References 60 publications
20
228
1
2
Order By: Relevance
“…Their analysis included protocols to account for rates-across-sites heterogeneity by use of specific partitioning models of sequence evolution among protein coding positions and RNA structures and, unlike in previous studies of mitochondrial DNA, ratite monophyly was not enforced. Their favoured analysis confirmed the topology found by Harshman et al (2008), in which ostriches were basal and tinamous embedded among ratites. However, they found tinamous to be very strongly supported as sister to moa and this combined clade sister to Australasian ratites.…”
Section: Analyses Of Molecular Data Post 2000supporting
confidence: 71%
See 3 more Smart Citations
“…Their analysis included protocols to account for rates-across-sites heterogeneity by use of specific partitioning models of sequence evolution among protein coding positions and RNA structures and, unlike in previous studies of mitochondrial DNA, ratite monophyly was not enforced. Their favoured analysis confirmed the topology found by Harshman et al (2008), in which ostriches were basal and tinamous embedded among ratites. However, they found tinamous to be very strongly supported as sister to moa and this combined clade sister to Australasian ratites.…”
Section: Analyses Of Molecular Data Post 2000supporting
confidence: 71%
“…Therefore, we will only compare our tree in detail to that of Phillips et al (2010) who, like us, used a range of neognaths to root their tree. As was first indicated by Hackett et al (2008) and Harshman et al (2008), Phillips et al (2010) found tinamous made ratites paraphyletic, and specifically were strongly supported as sister to moa. This appears to contrast greatly from our finding in Analysis 1 that tinamous constituted a basal branch in palaeognaths.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…), Kiwis (Apteryx spp. ), Moas, and Elephant birds; the debate is relevant to whether flightlessness in ratites evolved only once or several times independently (Harshman et al 2008, Phillips et al 2010, Baker et al 2014. Most recent results indicate a discrepancy between geographic location and phylogenetic relatedness among ratite species, suggesting that the major ratite lineages must have dispersed by flying before evolving converging anatomical characteristics and flightlessness (Mitchell et al 2014).…”
Section: Introductionmentioning
confidence: 99%